Agama sebagai king maker terhadap problematika gender equality di benua asia - Kencana Asih, Gek Dian; Maharani Putri, Angelica; Komala Putri Hartayani, Made Cindy (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Religion has a significant role in shaping the social values ​​and norms of society on the Asian continent. Religion can influence society's views regarding gender roles and relationships. In religious interpretations it limits gender equality, such as placing women in more limited roles and considering men dominant in the realms of leadership, public and politics. On the other hand, women are generally involved in domestic roles, which include tasks such as cooking, washing clothes, cleaning the house, caring for children, and carrying out daily activities in the house. However, not all religious interpretations limit gender equality. Many individuals and groups in religious contexts use religious values ​​to fight for gender equality and fight discrimination. So in this article, we will discuss the role of religion as an important decision maker regarding the issue of gender equality on the Asian continent. This research uses a descriptive qualitative approach using data collection techniques in the form of literature studies relevant to this research topic. The results of this research show that to maintain the existence of religion in Asia, it is very important to eliminate traditions that conflict with religious principles and advocate for gender equality. Religion has a significant role in regulating human life and pushing it towards the common good. However, it is important to update the understanding of gender in every religion in order to recognize and accept gender equality, as well as overcome discrimination against women.